2023
DOI: 10.1002/acn3.51832
|View full text |Cite
|
Sign up to set email alerts
|

CSF neopterin and quinolinic acid are biomarkers of neuroinflammation and neurotoxicity in FIRES and other infection‐triggered encephalopathy syndromes

Abstract: ObjectiveInfection‐triggered encephalopathy syndromes (ITES) are potentially devastating neuroinflammatory conditions. Although some ITES syndromes have recognisable MRI neuroimaging phenotypes, there are otherwise few biomarkers of disease. Early detection to enable immune modulatory treatments could improve outcomes.MethodsWe measured CSF neopterin, quinolinic acid, kynurenine and kynurenine/tryptophan ratio using a liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS) system. The CSF of 18 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have suggested that acid and the kynurenine-tryptophan pathway serve as neuroinflammation biomarkers. [40][41][42] A previous study has shown elevated levels of CSF quinolinic acid and kynurenine in patients with infectiontriggered encephalopathy syndrome, including febrile infection-related epilepsy syndrome (FIRES), which is a subgroup of refractory SE. This elevation could be linked to the excessive conversion of tryptophan into kynurenine by the IDO enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that acid and the kynurenine-tryptophan pathway serve as neuroinflammation biomarkers. [40][41][42] A previous study has shown elevated levels of CSF quinolinic acid and kynurenine in patients with infectiontriggered encephalopathy syndrome, including febrile infection-related epilepsy syndrome (FIRES), which is a subgroup of refractory SE. This elevation could be linked to the excessive conversion of tryptophan into kynurenine by the IDO enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…44 Exploring interventions such as tryptophan supplementation and kynurenic acid (an NMDA receptor antagonist) may prove beneficial in preventing SE-related consequences. 41,42 A recent study even demonstrated the usefulness of an IDO inhibitor in reducing the frequency of infantile spasms. 28 Although alterations in glutamate levels have been observed frequently in the serum of patients with epilepsy, 12,13,16 and in animal models, our study did not find significant differences in glutamate levels in either plasma or CSF samples.…”
Section: Discussionmentioning
confidence: 99%